The effect of soluble E-selectin on tumor progression and metastasis. Issue 1 (December 2016) - Kang, Shin-Ae; Blache, Celine; Bajana, Sandra; Hasan, Nafis; Kamal, Mohamed; Morita, Yoshihiro; Gupta, Vineet; Tsolmon, Bilegtsaikhan; Suh, Stephen; Gorenstein, David; Razaq, Wajeeha; Rui, Hallgeir; et al.
Abstract Background Distant metastasis resulting from vascular dissemination of cancer cells is the primary cause of mortality from breast cancer. We have previously reported that E-selectin expression on the endothelial cell surface mediates shear-resistant adhesion and migration of circulating cancer cells via interaction with CD44. As a result of shedding, soluble E-selectin (sE-selectin) from the activated endothelium is present in the serum. In this study, we aimed to understand the role of sE-selectin in tumor progression and metastasis. Methods We investigated the effect of sE-selectin on shear-resistant adhesion and migration of metastatic breast cancer cells and leukocytes in vitro and in vivo. Results We found that sE-selectin promoted migration and shear-resistant adhesion of CD44+ /high breast cancer cell lines (MDA-MB-231 and MDA-MB-468) to non-activated human microvessel endothelial cells (ES-HMVECs), but not of CD44-/low breast cancer cell lines (MCF-7 and T-47D). This endothelial E-selectin independent, sE-selectin-mediated shear-resistant adhesion was also observed in a leukocyte cell line (HL-60) as well as human peripheral blood mononuclear cells (PBMCs). Additionally, the incubation of MDA-MB-231 cells with sE-selectin triggered FAK phosphorylation and shear-resistant adhesion of sE-selectin-treated cells resulted in increased endothelial permeabilization. However, CD44 knockdown in MDA-MB-231 and HL-60 cells resulted in a significant reduction of sE-selectin-mediated shear-resistant adhesion to non-activated HMVECs, suggesting the involvement of CD44/FAK. Moreover, functional blockade of ICAM-1 in non-activated HMVECs resulted in a marked reduction of sE-selectin-mediated shear-resistant adhesion. Finally, the pre-incubation of CD44+ 4 T1 murine breast cancer cells with sE-selectin augmented infiltration into the lung in E-selectin K/O mice and infusion of human PBMCs pre-incubated with sE-selectin stimulated MDA-MB-231 xenografted breast tumor growth in NSG mice. Conclusions Our data suggest that circulating sE-selectin stimulates a broad range of circulating cells via CD44 and mediates pleiotropic effects that promote migration and shear-resistant adhesion in an endothelial E-selectin independent fashion, in turn accelerating tissue infiltration of leukocytes and cancer cells.